2020
DOI: 10.3390/nu12092795
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine’s Effect on the Biomarkers of Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: A systematic review and meta-analysis of randomized controlled trials (RCTs) was carried out to assess L-carnitine supplements’ influence on the biomarkers of metabolic syndrome (MetSyn). PubMed, EMBASE, Cochrane library, and CINAHL were used to collect RCT studies published prior to February 2020. RCT studies were included if they had at least one of the following biomarker outcome measurements: waist circumference (WC), blood pressure (BP), fasting blood sugar (FBS), triglyceride (TG), or high density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
(74 reference statements)
0
6
2
1
Order By: Relevance
“…This suggests that 6 months of use is a critical juncture and that physicians should ensure a duration of administration of at least six months when applying l -carnitine for glucose control improvement. Interestingly, we also found that l -carnitine supplement could effectively reduce FBG in people who are overweight without being obese (24 < BMI ≤ 28), which was not in accordance with Choi et al 32 A possible explanation is that the current work was performed without restrictions in specific disease or intervention, as well as included more RCTs comparing to Choi et al The physiological roles of l -carnitine may also help to explain that l -carnitine is primarily responsible for maintaining β-oxidation and overall energy balance of the body; 30,35 thus, l -carnitine supplementation is more likely to be effective when the energy balance is disturbed, such as when overweight. In addition, our previous studies also found that changes in the oxygen environment of the body only affected skeletal muscle l -carnitine redistribution in overweight mice but not in control animals.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…This suggests that 6 months of use is a critical juncture and that physicians should ensure a duration of administration of at least six months when applying l -carnitine for glucose control improvement. Interestingly, we also found that l -carnitine supplement could effectively reduce FBG in people who are overweight without being obese (24 < BMI ≤ 28), which was not in accordance with Choi et al 32 A possible explanation is that the current work was performed without restrictions in specific disease or intervention, as well as included more RCTs comparing to Choi et al The physiological roles of l -carnitine may also help to explain that l -carnitine is primarily responsible for maintaining β-oxidation and overall energy balance of the body; 30,35 thus, l -carnitine supplementation is more likely to be effective when the energy balance is disturbed, such as when overweight. In addition, our previous studies also found that changes in the oxygen environment of the body only affected skeletal muscle l -carnitine redistribution in overweight mice but not in control animals.…”
Section: Discussioncontrasting
confidence: 87%
“…Interestingly, we also found that L-carnitine supplement could effectively reduce FBG in people who are overweight without being obese (24 < Abbreviations: MD: mean differences, CI: confidence interval, FBG: fasting blood glucose, TG: triglycerides, TC: total cholesterols, LDLc: low−density lipoprotein-cholesterol, HDLc: high-density lipoprotein-cholesterol, BMI: body mass index, RCT: randomized controlled trial, DM: diabetes mellitus. Food & Function Paper BMI ≤ 28), which was not in accordance with Choi et al 32 A possible explanation is that the current work was performed without restrictions in specific disease or intervention, as well as included more RCTs comparing to Choi et al The physio-logical roles of L-carnitine may also help to explain that L-carnitine is primarily responsible for maintaining β-oxidation and overall energy balance of the body; 30,35 thus, L-carnitine supplementation is more likely to be effective when…”
Section: Blood Glucose and Insulin Resistancecontrasting
confidence: 57%
See 2 more Smart Citations
“…Subgroup analysis was performed to examine probable sources of heterogeneity, according to predefined variables including dosage (≤ 200 vs. > 200 mg/day) and duration (≤ 8 vs. > 8 weeks). For studies with missing values of SD for mean difference, the following formula was used: SD = square root ((SD pretreatment ) 2 + (SD posttreatment ) 2 − (2R × SD pretreatment × SD posttreatment )), where correlation coefficient (R) was assumed equal to 0.5 [ 26 ]. Effect sizes were expressed as the mean difference and 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%